UJI AKTIVITAS ANTIDIARE TABLET EKSTRAK ETANOL DAUN KATUK (Sauropus androgynus L.) Merr. PADA MENCIT PUTIH (Mus musculus) - Nurul Fadilah, Nitya; Melinia, Meena; Septiani Agustien, Gina (Jurnal Insan Farmasi Indonesia, 2023)
Diarrhea is a condition in which a person experiences excretion of feces more than 3 times a day accompanied by an increase in volume and diluÂÂtion which results in dehydration and even causes death. The aim this study was to determine the antidiarrheal activity of ethanol extract tablets of katuk leaves (Sauropus androgynus L.) Merr. which contains tannins, flavonoids and alkaloids as anti-diarrheal compounds because they can inhibit intestinal motility. This test uses the intestinal transit method which measures the length of the intestine through which the marker passes. The number of mice used was 25 which were divided into 5 groups. The positive control group 1 used loperamide HCl at a dose of 4 mg/kgBW. Group 2 was negative control with tablets without extract, Group 3 with tablet extract 80 mg/kgBW, group 4 tablets with extract dose 160 mg/kgBW and group 4 with tablet extract 320 mg/kgBW. The results of this test show that in formulation 1 it has an activity value of 40.32%, in formulation 2 it is 43.21% and in formulation 3 it is 45.2%. Tablet preparations with the best results were in formulation 3 with an extract dose of 320 mg/kgBW which showed the best results